High-temperature corrosion investigations of deposit containing eutectic KCl-K2SO4 mixture on AISI 1015 and SS304 steels. (15th August 2022) - Khantisopon, Kritkasem; Tharajak, Jirasak; Nawarat, Poomirat; Sanpo, Noppakun; Ang, Andrew S.M.
Abstract: This study investigated corrosion behaviours of biomass fly ash containing eutectic KCl-K2 SO4 mixture on carbon steel AISI 1015 and stainless steel 304 (SS304) at 700 ℃ for 12 h in air. The observed corrosion behaviours were validated by comparing with corrosion on similar materials, including carbon steel STBA 12 boiler tube and SS304 erosion guard, exposed in actual boiler environments. Similar corrosion behaviours were found in both laboratory-scale and field tests. Active oxidation, caused by chlorine, dominated over internal sulfidation for carbon steels. For SS304, presence of chlorine depleted protective oxide layers of SS304, followed by internal sulfidation from sulphur species. Graphical Abstract: ga1 Highlights: Investigation on steels corroded by biomass fly ash doped with eutectic KCl-K2 SO4 . Active oxidation by chlorine dominated over internal sulfidation on boiler steels. X-ray mapping showed deeper Cl penetration on carbon steels compared to sulphur. Similar corrosion behaviours were observed in both laboratory and field tests. The testing method may be utilised/modified for further hot corrosion experiments.